Study of the Effect of the Activity Level of the Enzyme Glucose-6-Phosphate Dehydrogenase with Some Electrolytes in Female Patients Suffering From Hemolytic Anemia in the City of Hilla - Mansoor, Sami Khlaif (American Journal of Bioscience and Clinical Integrity, 2025)
This "study aims to show the relationship between the level of the enzyme glucose-6-phosphate dehydrogenase and its relationship to electrolyte levels, which included (calcium, zinc, copper) in addition to vitamins (D, K). This study included 35 blood samples taken from patients suffering from anemia. Patients aged between (40-60) years and 35 samples as a control group (healthy people) for the period from (February to April 2024, when samples were collected from the chronic diseases unit of Al-Hilla Teaching Hospital in Babylon Governorate. The results of the current research showed a significant increase in each of the levels (calcium, copper) in the blood serums of patients with hemolytic anemia with a control group (healthy subjects), and the results also showed a significant decrease in each of the levels (G.6.P.D., zinc, vitamin D). (In the blood serums of patients with hemolytic anemia with a control group (healthy people) with no significant differences in the level of (vitamin K), and at its level the potential" for P ≤ 0.001.